Influence of the chinese culture on the negotiation process Peru-China - Acevedo Cueva, Nicole Alexandra (2020)
ABSTRACT This research is an intercultural study conducted with a deductive approach by generating theory-based questions derived from the socio-cultural framework of the Chinese business negotiation process, to be proved by the application of a self-managed open questionnaire on a sample of seven experienced Peruvian negotiators in negotiating with Chinese in order to determine how the Chinese negotiating culture influences the negotiation process. The results proved that the Chinese negotiating culture does influence the negotiating process according to the perception of 100% of the participating Peruvian negotiators and derives the following characteristics that a Peruvian negotiator could visualize and for which should be prepared during negotiations with Chinese to achieve success: the importance of knowing about the negotiating culture of the Chinese counterpart, the relevance of presenting exact information, the presence of an intermediary or mediator, the significance of socializing with the Chinese, the difficulty of negotiating the price, the slow and hierarchical Chinese decision-making process, the reluctant Chinese attitude to make concessions, the importance of signing a legal contract, and the Chinese tendency to renegotiate.